Atrial myxoma in early pregnancy. (18th April 2012) - Kither, HJ; Stephen, G; Vause, S
Abstract : Atrial myxoma is the most common primary cardiac tumour with a prevalence of 0.075% with a mean age for sporadic cases of 56 years. We report the case of a 30 year old primigravida who presented at 6+5 weeks pregnant with worsening dyspnoea and palpitations. Cardiac echo revealed a large left sided atrial myxoma causing outflow obstruction and mitral valve damage. The primary excision surgery required 84 minutes of cardiopulmonary bypass, and whilst successful, follow-up transthoracic echo revealed significant mitral valve regurgitation requiring valve replacement. This was performed with a bioprosthetic valve with 105 minutes of cardiopulmonary bypass. Post-operatively she remained in a pacing dependent rhythm and so had a permanent pacemaker sited. The first trimester was complicated with recurrent episodes of vaginal bleeding thought to be related to the heparin given at time of bypass. Routine anomaly ultrasound at 20 weeks gestation revealed a normal fetus but mild polyhydramnios and subsequent glucose tolerance testing found her to have gestational diabetes which was controlled with dietary measures. She was induced at 42 weeks gestation for post-maturity and had an emergency caesarean section for fetal distress. We report this case for its rarity – not only for the underlying disease process but for a successful pregnancy outcome following 2 prolonged periods of cardiopulmonary bypass in early pregnancy.